Land Use Land Cover Dynamics and its Impacts on Watershed: A Case Study of Mardi Watershed - Maskey, Reshma (Scientific Researches in Academia, 2023)
Located in western Nepal near Pokhara city, Mardi Khola watershed is a notable example of degradation in the middle-mountain region. No previous studies in the watershed have delved into identifying, analyzing and storing the bio-physical, environmental, social, economic and demographic information of the watershed to aid the development and timely update of its management and land use plan. Therefore, all watershed management activities in the watershed have resulted in underwhelming outcomes. This study highlighted the Land Use Land Cover (LULC) Change of Mardi watershed area, which has emerged as a significant environmental issue and its impacts on water resources availability at local level resources. LULC change analysis revealed land covers such as forest, built-up area and water bodies was increased while the area under agricultural land and barren land declined between 2001 and 2021. Furthermore, 61% of the households have perceived a decreased availability of water resources such as springs, rivers, and ponds in Mardi Khola watershed over the past few decades for various natural and anthropogenic reasons, which has not only affected the water availability, but overall environmental balance in the watershed. This study generalized the importance to synchronize scientific based watershed information for developing Watershed Management Information System (MIS) at national level to enable sustainable conservation and management of watershed resources of our country.